Characteristics of General Surgery Social Media Influencers on Twitter. Issue 3 (March 2021) - Elson, Nora C.; Le, Diana T.; Johnson, Mark D.; Reyna, Chantal; Shaughnessy, Elizabeth A.; Goodman, Michael D.; Lewis, Jaime D.
Background: The influence of social media and Twitter in general surgery research, mentorship, networking, and education is growing. Limited data exist regarding individuals who control the dialogue. Our goal was to characterize influencers leading the discussion in general surgery. Methods: Right Relevance Insight API was searched for "general surgery, " and individual influencers were ranked by a comprehensive assessment of connections (followers/following) and engagement (likes, retweets, and comments). Profession, specialty, gender, and location were collected utilizing Twitter, Doximity, LinkedIn, ResearchGate, and institutional websites. American Board of Surgery and Royal College of Physicians and Surgeons of Canada were queried for board certification and academic h -index scores were acquired from Scopus. Results: Eighty-eight individual influencers in general surgery were identified, with 73 holding positions in general surgery. Attending level general surgeons comprised 50%, of which 91% are board certified, and 94% completed a fellowship (surgical oncology, laparoscopic surgery, critical care/trauma, and colorectal surgery). Residents comprised 31%; 11% were nonsurgeons and 3% were not physicians. The majority of residents and fellow influencers were female (72%). Many general surgery influencers were international (51%), particularly Canadian (28% overall). The academic h -indices for these influencers (n = 73) ranged from 0 to 73 (mean 14.5 ± 8.2; median 9.5). Discussion: Our data describe the positions, backgrounds, and research contributions of the top Twitter influencers in general surgery. Those engaged in social media should consider the background, expertise, and motivation of these influencers as the utilization and impact of this platform grows.